Relational Themes in Counselling Supervision: Broadening and Narrowing Processes - Gazzola, Nicola; Thériault, Anne (Canadian Journal of Counselling and Psychotherapy, 2008)
This study investigated the experiences of broadening (i.e., thinking and acting creatively and being open to exploring new ways of being) and narrowing (i.e., the experience of perceiving one’s choices as limited) in the supervisory process with the aim of identifying key relational themes from the perspective of supervisees. We interviewed 10 novice counsellors using a semi-structured interview protocol in order to understand their perceptions of broadening and narrowing processes during their Master’s-level internships. Interviews were analyzed using a variation of the consensual qualitative research method (Hill, Thompson, & Williams, 1997). Three relational themes were abstracted: (a) the use of power, (b) the balance between challenge and support, and (c) the implementation of structure in the supervision. The findings have implications for counselling supervision practices as well as counsellor education.